The Effects of Hosting Events on Destination Branding: Dubai Expo 2020 - Sharma, Sarthak; Kleber, Daniel Marco-Stefan; StranjanÄeviÄ‡, Ana (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2019)
Background - This paper evaluates the effects of events on the destination brand of Dubai as it prepares to host the Expo 2020. Destination branding assists in understanding the cityâ€™s strong â€œassetsâ€ and their impact on the upcoming Expo.Purpose â€“ The purpose of the study is to understand how large events impact development of a cityâ€™s brand. Based on the results, conclusions can be made on whether the efforts for the Expo will have a lasting impact on Dubaiâ€™s destination brand.Methodology â€“ The methodology acquires information about the effects of hosting events on Dubaiâ€™s destination brand through the analysis of the Expo 2020. Primary research, primarily in-depth interviews, bring perspective from industry professionals about destination branding, event management, and their economic implications. The TourismÂ AreaÂ LifeÂ CycleÂ (TALC)Â and other comparative models are utilized to understand correlations and applications to the Expo 2020.Findings â€“ The paper considers the preliminary efforts of Dubai indicating the increased opportunities in the city and excitement in the global community. The results highlight that the successful initiation of Expo 2020 would display Dubaiâ€™s capability of hosting events, differentiating it from other cities, and presenting a positive outlook for the economy. Areas that will experience growth include Dubai as a major event venue, a major tourist destination, and an economic hub in the region.Research limitations â€“ This study has been conducted before the official commencement of the Expo 2020 and therefore it gives a â€œbefore the eventâ€ perspective only. It could be improved by assessing the visitor interest and attitudes after the event and making cause and effect models to develop comprehensive conclusions about the impact.Originality/value â€“ There are limited studies on this topic as World Expos are major events occurring in select cities with economic and infrastructural capabilities. The current research on the impact of events mainly focuses on sports or festivals. Expo 2020 has great importance to Dubai due to its economic and destination brand implications, confirming the uniqueness of the research. Based on the results, future studies can assess large-scale events around the world, present accurate information on the impacts of expos, and enrich destination branding studies.Keywords: Dubai, Destination Branding, Events, Expo 2020, World Expo